Using university rankings as a potential indicator of student experiences in American higher education. (2nd January 2019) - Heffernan, Troy A.
ABSTRACT: Students at America's most renowned private universities face different acceptance rates, college wealth, class sizes, and potential graduate earnings even in comparison with students at the nation's highest-ranking public institutions. The analyses that led to these findings frequently focused on national or state-wide comparisons of public versus private universities. This paper contrasts these studies by analysing a fixed group of colleges, those regularly listed in the global top 50 of research and reputation rankings. It argues that even within this small subset of colleges, the highest-ranking public universities have more in common with their similarly positioned private counterparts than with lower ranking public institutions; a finding reflected in assessments of private colleges. Subsequently, the paper finds that student experiences are more likely defined by a college's reputational rank than by an institution's public or private status, endowment, or acceptance rates, however, the same was found not to be true of potential graduate earnings.